The Future of Accounting and Finance: Trends and Challenges - Ariany, Vince (Accounting Studies and Tax Journal (COUNT), 2024)
This research investigates "The Future of Accounting and Finance: Trends and Challenges" using a systematic literature review method. From the analysis, it was found that technology adoption, paradigm shifts in performance measurement, transformation in business practices, treatment of cryptocurrencies, and involvement of transnational banks are the main trends that will influence accounting and financial practices in the future. The implications of these trends for business practices and economic policy are explained through a series of hypotheses proposed and analyzed. This research provides in-depth insight into the direction of development of the accounting and finance discipline and the challenges faced in the future.